The effect of social enterprise's capabilities towards scaling social innovation in Malaysia - Noor Raihani Zainol
Social enterprises have the potentials capabilities to generate greater social innovation to achieve an organisational growth that contributes back to the society. In fact, by applying social innovation, SEs providing workable solution as the ability to sustain the changes in the form of organisations, management, practices, and process. The importance of social innovation has increasingly been gaining attention due to the alternative method to solve societal crises for the long term and social development plans with well-prepared and intellectual methods to address the social issue in an effort to bring forward sources for sustainable growth. However, social enterprises in Malaysia are still operating less efficiently, lack of organisational capabilities and support towards social innovation in providing their product and services to the community. As the demand of social innovation has increased, SEs are expected to be effective and efficient in providing services to the society's well being. Social enterprises are supposed to have the ability to transform their organisational capabilities into effective capabilities in order to achieve sustainability in social innovation. Therefore, the purpose of this study is to examine the effect on social enterprises' capabilities, organisational support for innovation and social innovation and eventually proposing the scale model of social enterprises. The study employs quantitative method to deal with quantifying and analyzing variables in order to get the results. Purposive sampling technique is applied and has employed a cross-sectional design from 134 social enterprise respondents in Malaysia. The findings of the analysis use partial least squares (PLS) to examine the direct and mediating effects hypotheses. PLS assisted in testing the hypotheses that comprised of organisational capabilities, organisational support for innovation, and social innovation. Bootstrapping was later conducted to investigate the standard error of the estimate and t-values. The assessment of the path coefficient signs and also the significance of the path coefficients revealed the result for structural model in this research. The results indicated that only three path coefficients involved in this research, which are social enterprise capabilities and social innovation, social enterprise capabilitie and organizational support for innovation, and organizational support for innovation and social innovation. All this variables were found to be significantly positive for direct effect. Therefore, these relationships are found contingently upon scaling social innovation. The findings have led to some implications to social innovation of social enterprises in Malaysia. Social enterprises can expand their potentials by applying social innovation in serving customers or community. In fact, by encouraging and training their employees in innovative ways will produce knowledgeable employees who are able to manage social enterprises efficiently.